Effect carbon black and modified kaolin hybrid filler on the curing and physic-mechanical properties of natural rubber-styrene butadiene rubber blends. Issue 1 (January 2022) - Susanto, T; Rahmaniar; V Putra, V. G.; Sari, T I; Farida; Roni, K A; Puspitasari, G
Abstract: Carbon black is known as an excellent reinforced filler for rubber compounding, this petroleum based product needs to be substituted using renewable or mineral filler due to some negative adverse. In this paper, natural rubber (NR) – styrene-butadiene rubber (SBR) (50/50) phr binary blends based on polyethylene glycol-modified kaolin (PEG-K) and carbon black CB hybrid filler were synthesized. The rubber formulation was designed for idler roller for charcoal conveyor in open peat mining application. The present study investigates the effect of PEG-K and CB composition on curing, physical, tensile and oil, and acid resistance of the binary blends. The effect was examined by varying the composition of PEG-K/CB as follows: 50/0; 40/10; 30/20; 20/30; 10/40; 0/50 phr/phr of the hybrid filler. The rubber compounding was conducted in accordance with the ASTM D3142, and the testing procedures were analyzed based on international standards. The vulcanizates were prepared by heating press at 140 °C for about 25 minutes. The results showed that the processing-ability of a single filler is easier than the higher hybrid filler. The rheological analysis showed that the higher PEG-K may increase the cure rate index, but the lower PEG-K might improve cross-linking density. The higher loading CB improved the specific gravity and hardness, tensile strength slightly, while there is less significant effect on decreasing compression set, abrasion resistance, and elongation at break. Meanwhile, the higher number CB of binary blends has better oil and acid resistance than the PEG-K. Compared to idler roller specification in the market, the vulcanizates in this research have better quality.